Dasher can't wait for Christmas - Tavares, Matt (Candlewick Press, 2023)
"With only one sleep left before Christmas Eve, Dasher can't contain her excitement for her favorite holiday. With the sound of Christmas carols on the breeze and twinkling lights radiating from a nearby city, she sneaks off to visit the festivities. As night deepens and snow starts falling, Dasher realizes she can no longer spot the North Star in the sky to help guide her home. But thanks to a child, some Christmas spirit, and a special gift, she might be able to find her way home to the North Pole just in time for Christmas Eve."--